Curcumin Combined with FOLFOX Chemotherapy Is Safe and Tolerable in Patients with Metastatic Colorectal Cancer in a Randomized Phase IIa Trial - Howells, Lynne M; Iwuji, Chinenye O O; Irving, Glen R B; Barber, Shaun; Walter, Harriet; Sidat, Zahirah; Griffin-Teall, Nicola; Singh, Rajinder; Foreman, Nalini; Patel, Samita R; Morgan, Bruno; Steward, William P; et al. (The Journal of nutrition, 2019)
Curcumin is the main active ingredient of the spice turmeric, investigated extensively for putative anticancer properties. This phase IIa open-labelled randomized controlled trial aimed to assess safety, efficacy, quality of life, neurotoxicity, curcuminoids, and C-X-C-motif chemokine ligand 1 (CXCL1) in patients receiving folinic acid/5-fluorouracil/oxaliplatin chemotherapy (FOLFOX) compared with FOLFOX + 2 g oral curcumin/d (CUFOX). Twenty-eight patients aged >18 y with a histological diagnosis of metastatic colorectal cancer were randomly assigned (1:2) to receive either FOLFOX or CUFOX. Safety was assessed by Common Toxicity Criteria-Adverse Event reporting, and efficacy via progression-free survival (PFS) and overall survival (OS). Quality of life and neurotoxicity were assessed using questionnaires (European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-C30 and Functional Assessment of Cancer Treatment-Gynecologic Oncology Group-Neurotoxicity). Plasma curcuminoids were determined with liquid chromatography (LC) electrospray ionization tandem mass spectrometry and CXCL1 by ELISA. Addition of daily oral curcumin to FOLFOX chemotherapy was safe and tolerable (primary outcome). Similar adverse event profiles were observed for both arms. In the intention-to-treat population, the HR for PFS was 0.57 (95% CI: 0.24, 1.36; P = 0.2) (median of 171 and 291 d for FOLFOX and CUFOX, respectively) and for OS was 0.34 (95% CI: 0.14, 0.82; P = 0.02) (median of 200 and 502 d for FOLFOX and CUFOX, respectively). There was no significant difference between arms for quality of life (P = 0.248) or neurotoxicity (P = 0.223). Curcumin glucuronide was detectable at concentrations >1.00 pmol/mL in 15 of 18 patients receiving CUFOX. Curcumin did not significantly alter CXCL1 over time (P = 0.712). Curcumin is a safe and tolerable adjunct to FOLFOX chemotherapy in patients with metastatic colorectal cancer. This trial was registered at clinicaltrials.gov as NCT01490996 and at www.clinicaltrialsregister.eu as EudraCT 2011-002289-19.